A Universal Approach for Maximizing Terahertz Wave Absorption in Graphene Cut-Wires - Zhu, Hongjia; Wang, Ximiao; Cao, Zhaolong; Chen, Huanjun; Deng, Shaozhi (Frontiers in Materials, 2021)
Graphene micro-/nanostructures and their arrays have attracted considerable attention in infrared (IR) and terahertz (THz) applications due to their strong plasmon responses. However, as too many parameters, including geometry, carrier concentration, frequency, and adjacent substrate, can affect the plasmonic behaviors of the micro-/nanostructures, the optimization of the THz-IR responses, such as absorption and reflection, of these structures and their arrays require tremendous computations on parameter scanning. Here, we propose a theoretical approach to design graphene cut-wires with maximized THz wave absorption. Analytical expression describing the THz absorption/reflection of graphene cut-wires is derived. Accordingly, a maximum THz wave absorption of the array, regardless of its operating frequencies and geometrical parameters, can be achieved by simply tuning the cut-wires duty ratio. The analytical results are further validated by numerical simulations. This intuitive design manner is of significance for the design of graphene arrays with high-efficiency THz responses as well as promoting their practical applications in THz functional devices.